2005
DOI: 10.1016/j.jhsb.2005.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Function and Sensitivity Utilizing a Homodigital Neurovascular Island Flap after Amputation Injuries of the Fingertip

Abstract: Sixty-three fingertip amputations in 50 patients were reconstructed using a homodigital neurovascular island flap technique based on a single neurovascular pedicle without further shortening of the distal phalanx. The procedure was carried out under regional anaesthesia, using a tourniquet and magnifying loupes. All of the flaps survived and achieved normal or adequate two-point discrimination without any painful scar or cold hypersensitivity. Fifteen patients had some loss of distal interphalangeal joint exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 19 publications
2
25
0
3
Order By: Relevance
“…9% of our studies (n=4) reported pinch strength. 17,23,28,39 Mean pinch strength was 3 ± 1 kg (n=2), ranging from 2–5 kg (Table 5). 17,39 Overall, local flaps outperformed revision amputation in preserving PIP AOM, but slightly underperformed in preservation of TAM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…9% of our studies (n=4) reported pinch strength. 17,23,28,39 Mean pinch strength was 3 ± 1 kg (n=2), ranging from 2–5 kg (Table 5). 17,39 Overall, local flaps outperformed revision amputation in preserving PIP AOM, but slightly underperformed in preservation of TAM.…”
Section: Resultsmentioning
confidence: 99%
“…26,30,31,35,37,54,56 16% of our studies (n=7) evaluated cosmetic satisfaction. 17,21,27,39,43,45,55 85% of patients (112/131) reported “satisfactory” ratings and 98% of patients (105/107) reported “good” or “excellent” ratings, irrespective of treatment. 9% of our studies (n=4) evaluated other PRO measures, such as the Disabilities of the Arm, Shoulder, and Hand (DASH) score.…”
Section: Resultsmentioning
confidence: 99%
“…The maximal advancement of this flap has been reported to be in the range of 15–22 mm (Adani et al., 1997; Arsalan-Werner et al., 2019; Borman et al., 2000; Evans and Martin, 1988; Foucher et al., 1989; Lanzetta et al., 1995; Lok et al., 2017; Massart et al., 1985; Sano et al., 2008; Schuind et al., 1985; Usami et al., 2015, Varitimidis et al., 2005; Wang et al., 2011), which is summarized in Table 3. We have noted some deficiencies in the previous articles on homodigital neurovascular island flaps.…”
Section: Discussionmentioning
confidence: 98%
“…These seemingly mundane injuries represent a significant cost to society and to the affected individuals for treatment and from losses due to decreased production. Persistent cold intolerance [1, 8, 23–25], tenderness, and disfigurement [1, 8, 11] may have a major long-term impact on personal and professional activities [26]. In each case, the final outcome depends to some degree on the initial treatment, which may cause more disability than the injury itself.…”
Section: Discussionmentioning
confidence: 99%